Information on mouth breathing in children and adolescents’ mothers - Silvia Maholy Vera Torres; Genesis Magerly García Noguera; Jaime Fernando Armijos Moreta; Silvia Marisol Gavilánez Villamarín (Medisur)
Background: the mouth breather syndrome is more common than it seems; most people suffer from it, but affects frequently children and adolescents. Objective: to determine the information about mouth breathing in children and adolescents’ mothers. Methods: a descriptive, cross-sectional study was carried out during from January the 1st, 2022 to March the 31st, 2022, in the El Prado neighborhood, Santo Domingo de los Tsachilas, Ecuador. Non-probabilistic sampling was used taking into account the inclusion criteria: being mothers of children between 5 and 14 years of age and agreeing to participate in the research. The sample was made up of 21 mothers. The data was collected through a survey. The variables were: knowledge about mouth breathing and the child's permanence with the mouth open during the day. Results: 67% of the mothers surveyed answered that they had no knowledge about mouth breathing or about the health disorders that it could cause to their children. 81% of children do not remain with their mouths open during the day. Conclusions: research on this topic is important because the earlier this disease is diagnosed, the easier it will be to correct.